Greenland, view of Kjerulf Fjord through to Dicksons Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
Kjerulfs [Kjerulf] Fjord thru [through] to Dickson[Fjord] Fjord. Hisinger Glacier [Hisinger Gletscher].